Improving Access to Hormonal Contraception Methods. Issue 2 (March 2020) - Killion, Molly M.
Abstract : Over-the-counter access to hormonal contraceptive methods is safe and can help women prevent unintended pregnancy. Our maternity nursing expert, Molly Killion, presents an overview of the recent committee opinion on this topic from our colleagues at the American College of Obstetricians and Gynecologists.